A Reusable TNF-Tagged Chiral Bis(oxazoline)–Copper Catalyst for Diels– Alder Transformations - Didier, Dorian; Schulz, Emmanuelle (Synlett, 2012)
A chiral bis(oxazoline) ligand, substituted on the methylene bridge by a covalent link to an electron-deficient moiety (2,4,7-trinitrofluoren-9-one, TNF), is a useful ligand associated to copper(II) salts to promote enantioselective Diels–Alder reactions between N-acyloxazolidinones and cyclopentadiene. Owing to different solubility properties, the corresponding catalyst was precipitated by pentane addition after reaction completion and was easily recovered by filtration. It was successfully reused in up to 20 successive catalytic cycles for the formation of the targeted products with no loss of either the activity or the enantioselectivity along with the recycling.
Keywords: asymmetric catalysis; charge transfer complexes; copper; Diels–Alder reaction; catalyst recovery